Enterprise Architecture Design For Creative Project Management Systems Kuy Studio Uses The Zachman Framework - Fajar Mahayoga; Indah Rahmayani (oneamrd (One a Mllions Dreams Corporation), 2025)
Kuy Studio as a creative company faces challenges in managing complex and collaborative projects. The absence of a structured information system leads to suboptimal workflows, coordination, and supervision of projects. This research aims to design an enterprise architecture using the Zachman Framework to support a creative project management system that suits the needs of the organization. This approach accommodates all aspects of the organization from a business standpoint to technical implementation. The results of this research are in the form of an enterprise architecture blueprint that maps business processes, information, and IT infrastructure in an integrated manner. This design is expected to be the foundation for the development of effective and efficient systems in the future.